Hardware in the loop experiments on the interaction between a diesel-mechanical propulsion system and a ventilating propeller - Huijgens, Lode; Vrijdag, Arthur; Hopman, Hans (Journal of marine engineering and technology, 2023)
The interaction between ship propulsion machinery, propellers and the highly dynamic environment which is the sea is a complex yet highly relevant subject. During a storm, for example, waves and ship motions may cause the propeller to draw air, or ventilate, resulting in rapid changes in propeller thrust and load torque. These fluctuations propagate through the propulsion system, potentially causing excessive loads on propulsion machinery, while also reducing the ship's manoeuvrability. A profound understanding of these complex interactions still lacks. One result of this knowledge gap is the limited acceptance of new technologies for ship propulsion, especially those technologies known to have limited transient capabilities. In this paper, hardware in the loop (HIL) is proposed as a solution to this knowledge gap. Paying specific attention to propeller ventilation, HIL is used to identify new aspects of interaction between engine and propeller, thus demonstrating the added value of HIL for ventilation studies.